Leprosy in England and Wales 1953–2012: surveillance and challenges in low incidence countries. Issue 5 (3rd May 2016) - Fulton, Nicholas; Anderson, Laura F; Watson, John M; Abubakar, Ibrahim
Abstract : Objective: To review all notified cases of leprosy in England and Wales between 1953 and 2012. Design: National surveillance study of all reported cases. Setting: England and Wales. Outcome: Number and characteristics of reported cases. Results: During this period, a total of 1449 leprosy cases were notified. The incidence fell from 356 new cases notified between 1953 and 1962 to 139 new cases between 2003 and 2012. Where data were available, leprosy was more common in men, 15–45 year olds and those from the Indian subcontinent. There was considerable undernotification in 2001–2012. Conclusions: The high level of under-reporting indicates a need for improved surveillance in the UK. Public Health England, in collaboration with the UK Panel of Leprosy opinion, has revised the UK Memorandum on Leprosy in order to provide updated guidance on diagnostic procedures, treatment, case management, contact tracing and notification.